Cord Blood Cells for Developmental Toxicology and Environmental Health - Il’yasova, Dora; Kloc, Noreen; Kinev, Alexander (Frontiers in Public Health, 2015)
The Tox21 program initiated a shift in toxicology toward in vitro testing with a focus on the biological mechanisms responsible for toxicological response. We discuss the applications of these initiatives to developmental toxicology. Specifically, we briefly review current approaches that are widely used in developmental toxicology to demonstrate the gap in relevance to human populations. An important aspect of human relevance is the wide variability of cellular responses to toxicants. We discuss how this gap can be addressed by using cells isolated from umbilical cord blood, an entirely non-invasive source of fetal/newborn cells. Extension of toxicological testing to collections of human fetal/newborn cells would be useful for better understanding the effect of toxicants on fetal development in human populations. By presenting this perspective, we aim to initiate a discussion about the use of cord blood donor-specific cells to capture the variability of cellular toxicological responses during this vulnerable stage of human development.